(3cTGa EUWdGMGJ Gdafhf hGdYdhes - (3eMeO Ydj Hf Ydj Hf bGVj eMeO MGeO GdJgGfhj GdgfOjs
(3ChdgG (B:s
(3GdCUe HJTOjO Gdeje Ydi bSe ef GdLPQ ebGHd ddefWb ceG YQaJ ai aUd GdQGA s
(3BNQgG (B:s
(3HhVY ChaGb UZjQI ahGFO YLjHI hZQjHI hGdMeO ddg Ydi Pdc s
(3GdejcQhajde Je JbSjeI Ydi YdHJjf (B( (3C (B, (3H (B) (3hgPG gh GdYdHI Hs
(3GdfSNI HgG MhGT s
(3HgG fXGe GdJYbjHI s
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3aQZ GdeDda ef JCdjaI SfI (B1158(3g`s
(3bQf GdfSN (B:s
Keywords: (3GdeYGQa GdYGeIs